Responsibilities of the non-state actor in armed conflict and the market place : theoretical considerations and empirical - Gal-Or, Noemi; Ryngaert, Cedric; Noortmann, Math (Koninklijke Brill, 2015)
To whom are armed opposition groups and business corporations accountable for their actions in armed conflict and in peace times? Are they responsible as a group? This pioneer book offers innovative theoretical and empirical analyses to these questions.